2003
DOI: 10.1097/01.icl.0000060998.20142.8d
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Tear Film Lipid Layer Thickness Following Treatment with Warm Compresses in Patients with Meibomian Gland Dysfunction

Abstract: Warm, moist compress therapy applied to the skin of the closed eyelids increases TFLLT for subjects with MGD by more than 80%, 5 minutes after initiating treatment and an additional 20% after 15 minutes of treatment. This study supports clinical experience and previous reports on warm, moist compress therapy as an effective treatment for meibomian gland dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 23 publications
(48 reference statements)
0
128
0
8
Order By: Relevance
“…10,14 Warm compresses prior to lid massage and omega-3 supplementation were added to patients with MGD, history of chalazia and hordeolum. 14,[19][20][21][22][23] Omega-3 supplementation may have an adjunctive effect on the management of MGD and inflammatory dry eye. [22][23][24][25][26][27][28][29][30][31] It has been shown that omega-3 modulate prostaglandin metabolism toward anti-inflammatory prostaglandin (PGE 3 ) synthesis due to competitive inhibition of the arachidonic acid pathway at the cyclo-and lipooxygenase level.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 Warm compresses prior to lid massage and omega-3 supplementation were added to patients with MGD, history of chalazia and hordeolum. 14,[19][20][21][22][23] Omega-3 supplementation may have an adjunctive effect on the management of MGD and inflammatory dry eye. [22][23][24][25][26][27][28][29][30][31] It has been shown that omega-3 modulate prostaglandin metabolism toward anti-inflammatory prostaglandin (PGE 3 ) synthesis due to competitive inhibition of the arachidonic acid pathway at the cyclo-and lipooxygenase level.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MGD, the meibum has an altered chemical structure that increases its melting point compared to the physiological 32 • C [2,9,10]. The exact melting point of meibum in those suffering from MGD has yet to be determined, as the chemical composition of the secretions is variable and in turn affects its physical attributes [11].…”
Section: Introductionmentioning
confidence: 97%
“…Following treatment, subjects reported symptomatic relief and showed an increase in tear film lipid layer thickness and less solidified sebum. In another study of 20 patients with dry eye associated with MGD, an increase in tear film lipid layer thickness was demonstrated following the application of warm moist compresses [14]. There are commercially available microwavable eyelid masks, which maintain warm temperatures far longer than wet washcloths.…”
Section: Manual and Mechanical Techniquesmentioning
confidence: 97%